Meningkatkan Perencanaan Karir Menggunakan Layanan Bimbingan Klasikal Dengan Metode Galerry Walk Pada Siwa SMA. - any anjany (Prodi Bimbingan dan Konseling universitas PGRI Semarang, 2025)
This study was motivated by the low level of career planning among students of class X.3 at SMA Negeri 7 Semarang. Based on the results of the Student Needs Assessment Questionnaire (AKPD), 2.90% or 24 out of 36 students expressed uncertainty in choosing their future goals or careers. The purpose of this study was to determine the effectiveness of classical guidance services using the discussion method in improving students' career planning. The study employed a classroom action research approach, conducted in two cycles, with each cycle consisting of two actions. The research subjects were 36 students, and data were collected using a career planning scale that had been tested for validity and reliability. Data were analyzed using descriptive quantitative methods. The results showed an improvement in students’ career planning after receiving the guidance services. In the first cycle, the achievement reached 75%, and increased to 87% in the second cycle. This indicates an 11% improvement from the first to the second cycle, and a total increase of 19% compared to the initial data.